THU0769-HPR Scope for biologic prescribing cost saving initiatives within the rheumatology department. (15th June 2017) - Heaton, R; Nasralla, J; Ismail, A; Brooks, A; Mercer, L; Filer, C
Abstract : Background: The rheumatology department at Stepping Hill Hospital prescribes biologic treatment for 400 inflammatory arthritis patients via external Homecare services. Significant resultant drug waste in the event of drug discontinuation is anticipated. 1 The initiation of a pro-active telephone call at three months, to capture and act upon primary inefficacy and non-tolerance has been considered as a potential alternative method for waste reduction. Objectives: Establish the baseline level of biologic drug waste (via Homecare) following cessation of biologic treatment. Review whether a proactive phone call (and subsequent limitation of supply if appropriate) prior to the three month review at the start of biologic therapy can help reduce biologic waste. Establish whether there is scope to implement other initiatives to reduce waste in the department. Methods: Patients who had stopped or switched biologic treatments delivered through Homecare providers were identified using the trust's biologic database and clinic records. Information on biologic delivery quantities and schedule were provided by Homecare companies. Data was analysed used Microsoft Excel®; number (and cost in accordance with pharmacy tariffs) of doses "wasted" was calculated by referring the date of treatment cessation with the date and quantity of last biologics deliveries and patient stock levels as reported by the homecare company. Doses obtained free of charge were excluded. Baseline data was captured over a six month period. Four costs were calculated; (1) Total waste. (2) Wasted supply exceeding two months to assess whether an increase in delivery frequency to two monthly could reduce waste. (3) Waste from unopened deliveries to establish whether waste could be reduced by improved patient education around refusing deliveries in the event of treatment failure or intolerance. (4) Waste from the second biologic prescription issued as a result of stopping biologic at the three month review to assess viability of the proactive phone. A proactive patient phone call was then initiated and waste data captured for a three month period following this intervention. Results: 27 patients stopped treatment during the 6 months baseline data collection. 23 patients had drug waste totalling £ 32, 140.80. The total value of wasted stock exceeding two months supply was £ 5, 414.36. Three patients accepted deliveries for further supply and stopped treatment before opening final deliveries, creating a waste total of £ 5, 509.09. Four patients stopped treatment at their three month review, £ 4, 572.22 of additional biologic was supplied and then wasted as a result. Following the pro-active phone call intervention, 21 patients were contacted before their second supply was due and supply subsequently limited for 8 patients, four of whom stopped treatment at their next consultant review. Limiting supply in the four patients saved £ 6, 682. Conclusions: Initiating a proactive phone call at three months following biologic initiation can reduce drug waste. Other initiatives such as patient education to refuse deliveries and increasing delivery frequency also appear viable waste reduction initiatives. References: Whiteman J, McVeigh O, Watters M. Hospital Pharmacy and the Pharmaceutical Industry Collaborate to Reduce Waste of Biologic Medicine. Rheumatology. 2016 Apr 1;55. Disclosure of Interest: None declared